2014
DOI: 10.1186/1746-4269-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoveterinary herbal remedies used by farmers in four north-eastern Swiss cantons (St. Gallen, Thurgau, Appenzell Innerrhoden and Appenzell Ausserrhoden)

Abstract: BackgroundVery few ethnoveterinary surveys have been conducted in central Europe. However, traditional knowledge on the use of medicinal plants might be an option for future concepts in treatment of livestock diseases. Therefore the aim of this study was to document and analyse the traditional knowledge and use of homemade herbal remedies for livestock by farmers in four Swiss cantons.MethodsResearch was conducted in 2012. Fifty farmers on 38 farms were interviewed with the aid of semistructured interviews. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 26 publications
4
47
0
8
Order By: Relevance
“…In Anlehnung an die Erfassungsmethodik vorhergehender Studien [6,7,8,9,10] wurden Pferdebesitzer aus dem Kundenstamm der Pferdepraxis Animal Support AG Ersigen (Kanton Bern) über das geplante Projekt informiert und gebeten, hierbei vorhandenes Erfahrungswissen einfließen zu lassen. In Form von spontanen Rückmeldungen wurden 7 Interviewpartner im Alter von 24-65 Jahren von pferdehaltenden Betrieben des Kantons Bern für das Projekt gefunden.…”
Section: Probanden Und Methodenunclassified
See 3 more Smart Citations
“…In Anlehnung an die Erfassungsmethodik vorhergehender Studien [6,7,8,9,10] wurden Pferdebesitzer aus dem Kundenstamm der Pferdepraxis Animal Support AG Ersigen (Kanton Bern) über das geplante Projekt informiert und gebeten, hierbei vorhandenes Erfahrungswissen einfließen zu lassen. In Form von spontanen Rückmeldungen wurden 7 Interviewpartner im Alter von 24-65 Jahren von pferdehaltenden Betrieben des Kantons Bern für das Projekt gefunden.…”
Section: Probanden Und Methodenunclassified
“…1). Selbstgemachte alkoholische Extrakte wurden im Gegensatz zu vorhergehenden Studien [5,6,7,8,9,10] von den Berner Pferdehaltern nicht genannt. Zum Einsatz kamen jedoch auch kommerziell erhältliche Fertigprodukte.…”
Section: Ergebnisse Und Diskussionunclassified
See 2 more Smart Citations
“…The present study revealed 60 plant species of 32 families used in the treatment of cattle diseases whereas Ninetyfour plant species belonging to 50 plant families were mentioned by Disler et al (2014). The main plant families were Leguminosae, Combretaceae, and Rubiaceae as also mentioned by Hilou et al (2014) (Toyang et al, 2007) and even the whole plant in the case of a herbaceae (Byavu et al, 2000) are used in traditional medicine.…”
Section: Plants Used In the Treatment Of The Enumerated Pathologiesmentioning
confidence: 99%